2011
DOI: 10.17159/2078-516x/2011/v23i2a354
|View full text |Cite
|
Sign up to set email alerts
|

The female athlete triad: a current concepts review

Abstract: Female athletic participation continues to grow throughout the world. This has many positive effects on health and well-being, but it has also led to a unique set of health problems. The female athlete triad was first described in 1992 by the American College of Sports Medicine, consisting of disordered eating, amenorrhoea and osteoporosis. An updated position stand was released in 2007 that modified the components of the triad to energy availability, menstrual function and bone mineral density. This article r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Furthermore, similar to the present study's findings, higher EDE-Q scores have been reported in females compared to males (Darcy et al, 2013), suggesting that female athletes may be at greater risk of disordered eating and subsequent LEA risk. The non-significant difference in potential LEA risk between type of sports (individual, team, or both) supports the understanding that the prevalence of the LEA and Triad is not merely limited to sports with emphasis on leanness and aesthetics (George, Leonard and Hutchinson, 2011).…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, similar to the present study's findings, higher EDE-Q scores have been reported in females compared to males (Darcy et al, 2013), suggesting that female athletes may be at greater risk of disordered eating and subsequent LEA risk. The non-significant difference in potential LEA risk between type of sports (individual, team, or both) supports the understanding that the prevalence of the LEA and Triad is not merely limited to sports with emphasis on leanness and aesthetics (George, Leonard and Hutchinson, 2011).…”
Section: Discussionsupporting
confidence: 52%
“…In this respect, it is worth mentioning the female athlete triad (isolate or combined presence of amenorrhea, impaired bone mass, and eating disorders), with each component existing on a spectrum from optimal health to disease. This condition, arising from low energy availability, mainly affects girls practicing sports that require leanness [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…of increasing PA in several key public health areas identified by review articles [1,[12][13][14]. These include cardiovascular disease, hypertension, obesity, type 2 diabetes, breast cancer, colon cancer, rheumatoid arthritis, pregnancy, chronic obstructive pulmonary disease, osteoarthritis, osteoporosis and depression.…”
Section: Review Processmentioning
confidence: 99%